Urinary Tract Infections - A Real Matter of Concern Regarding Preterm Delivery in Pregnant Females - Asma Akhtar, Bushra Khan, Maniha Anam, Sadia Faiz, Maria Khan, Sharmeen Kouser (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out prevasiveness of urinary tract infections in pregnant females who undergo premature deliveries. Design: Cross sectional study Setting: The study was conducted in Obstetrics and Gynaecology Deptt. Nishtar Hospital Multan. Duration of study: Six months (01-12-2017 to 01-05-2018). Subjects and Methods: Patients fulfilling the inclusion criteria and who underwent preterm deliveries in labour room, unit 1 were included in the research. 357 pregnant women who delivered prematurely were included in our research. Midstream urine samples were collected in sterilized bottles and was immediately shifted to pathology laboratory for culture and sensitivity. Results: Gestational Age Mean of patients noted to be 29.98 ± 2.29 weeks and 219 (61.3%) were 30 wks pregnant . Mean age of pregnant females was 27.47 ± 3.97 years (varied b/w 20 – 37 yrs ). Out of 357 pregnant ladies, 97 (27.2 %) were from villages and 260 (72.8 %) lived in cities. Earning per month , up to 30000 Rs. was noted in 206 (57.7%) while > 30000 Rs. Observed in 151 (42.3%). Mean BMI noted was 25.9 ± 1.38 kg/m2 and 109 (30.5 %) were obese . Out of 357 pregnant females, urinary tract infection was found in 137 (38.3%) patients undergoing preterm labor. Conclusion: Urinary tract infection ( UTI ) was commonly found among women undergoing preterm labor. Urinary tract infection had significant association with GA, age, residence , monthly earning, obesity, parity & literacy. Clinicians treating such patients undergoing preterm labor should always be vigilant for these infections as early detection and prompt treatment will decrease disease related morbidity and improve perinatal outcomes.